Polishing pad and manufacturing method of semiconductor device

By using a polyurethane substrate polishing layer with specific thermal conductivity and density characteristics in the polishing pad, combined with the buffer layer, the structure of the polishing pad is optimized, and the problems of CMP technology in global planarization and grinding rate inhomogeneity are solved, and efficient surface planarization and low defect rate of semiconductor devices are achieved.

CN119567090APending Publication Date: 2025-03-07HUBEI DINGHUI MICROELECTRONICS MATERIALS CO LTD +2

Patent Information

Application Number
CN202311141044.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-05
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When the existing CMP technology is used to process semiconductor devices, it is difficult to achieve global flattening, resulting in insufficient accuracy and resolution of photolithography affecting the transfer, and high grinding rate unevenness and defect frequency.

Method used

The closed-cell elastomer polishing layer formed by a polyurethane substrate with pore separation continuous is used, and combined with the buffer layer, the structure of the polishing pad is optimized to improve the polishing performance by controlling the thermal conductivity, density uniformity, groove shape and volume of the polishing layer.

Benefits of technology

It achieves a low grinding rate inhomogeneity and the number of defects, improves the comprehensive polishing performance of the polishing pad and ensures high-precision planarization of the surface of semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119567090A_ABST
    Figure CN119567090A_ABST
Patent Text Reader

Abstract

The invention relates to a manufacturing method of a polishing pad and a semiconductor device, the heat conductivity of a polishing layer is controlled to be between 0.04 W / (m.K) and 0.075 W / (m.K), the ratio of the density SG1 of any point of the polishing layer in the diameter direction to the minimum density SG0 of the polishing layer in the diameter direction is between 1.002 and 1.096, a groove is engraved in the surface of the polishing layer, and the thickness of the groove is smaller than that of the polishing layer. The groove shape comprises one or more of a concentric circle groove, a radioactive ray groove, an arc-shaped groove, an X-Y grid groove and a dot matrix punching groove, the ratio (V0-V) / V0 of the difference value of the volume V0 of the polishing layer before grooving and the volume V of the polishing layer after grooving to the volume V0 of the polishing layer before grooving ranges from 0.02 to 0.19, and the prepared polishing pad has excellent comprehensive polishing performance. The NU (Non-Uniformity) of the grinding rate is relatively small, and the defect is relatively small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polishing of chemical mechanical planarization treatment, and in particular to a polishing pad and a method for manufacturing a semiconductor device. Background Art

[0002] CMP technology is a technology that places the surface of the workpiece to be processed downward, applies pressure to the polishing pad with a certain pressure, and uses the relative movement of the polishing pad and the workpiece under the condition of flowing polishing liquid medium (a mixture of nanoparticles, chemical oxidants and liquid medium) to complete the material removal on the surface of the workpiece under the mechanical grinding of nanoparticles and the chemical corrosion of oxidants, thereby obtaining a global flattening technology of the workpiece surface. As the semiconductor industry changes along the curve of Moore's Law, the trend of processing technology is shifting towards higher current density, higher clock frequency and more interconnection layers. Due to the reduction of the size of the chip and the reduction of the focal depth of optical lithography equipment, the flatness of the chip surface that can accept resolution is required to reach the nanometer level. Traditional planarization technologies such as selective deposition based on deposition technology, sputtered glass SOG, low-pressure CVD, plasma-enhanced CVD, bias sputtering and post-sputtering corrosion, thermal reflow, deposition-corrosion-deposition, etc., although they can also provide a "smooth" surface, are all local flattening technologies and cannot achieve global flattening. It is generally believed internationally that when the device feature size is below 0.35μm, global planarization must be performed to ensure the accuracy and resolution of lithography effect transfer. CMP technology is currently recognized internationally as the only technology that can provide global planarization. The yield of CMP seriously affects the yield of chips.

[0003] As people need devices with higher operating speeds, lower leakage currents and less energy consumption, the manufacturing of semiconductor devices has become increasingly complex, which means that the devices require finer feature geometries and more metallization levels. These increasingly stringent design requirements have prompted people to use smaller line spacings. As the devices become smaller in size and more complex, the requirements for CMP technology become higher. In addition, as the feature size of integrated circuits decreases, defects caused by CMP, such as scratches, and grinding rate non-uniformity become bigger problems. Summary of the invention

[0004] The object of the present invention is to provide a polishing pad with excellent comprehensive polishing performance.

[0005] A first aspect of the present invention provides a polishing pad, comprising a polishing layer, wherein the polishing layer is a closed-cell elastomer formed of a polyurethane substrate having continuous pore separation, wherein the thermal conductivity of the polishing layer is between 0.04 W / (m·K) and 0.075 W / (m·K), wherein the ratio of the density SG1 of any point along the diameter direction of the polishing layer to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.096, wherein the surface of the polishing layer is engraved with grooves, wherein the groove shapes include: concentric circle grooves, radial grooves, arc grooves, XY grid grooves, and dot matrix punching grooves, wherein the difference between the volume V0 of the polishing layer before the grooves and the volume V after the grooves and the ratio (V0-V) / V0 of the volume V0 of the polishing layer before the grooves are between 0.02 and 0.19;

[0006] Preferably, the thermal conductivity of the polishing layer is between 0.048 W / (m·K) and 0.065 W / (m·K);

[0007] Furthermore, the density of the polishing layer is between 0.4 g / cm 3 ~0.73g / cm 3 between;

[0008] Preferably, the density of the polishing layer is between 0.4 g / cm 3 ~0.65g / cm 3 between;

[0009] Furthermore, the tensile strength of the polishing layer is between 2MPa and 18MPa;

[0010] Preferably, the tensile strength of the polishing layer is between 7MPa and 14.5MPa;

[0011] Further, the ratio of the density SG1 of any point along the diameter direction of the polishing layer to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.075;

[0012] Furthermore, the ratio (V0-V) / V0 of the volume V0 of the polishing layer before grooving and the volume V after grooving is between 0.02 and 0.145;

[0013] Furthermore, the polyurethane substrate is obtained by reacting a multifunctional isocyanate, a polyol and a curing agent;

[0014] The multifunctional isocyanate comprises one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, m-xylylene diisocyanate, ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate;

[0015] The polyol comprises one or more combinations of polytetramethylene ether glycol, polyethylene glycol, polypropylene glycol, ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, homopolymers and / or copolymers of ethylene oxide and propylene oxide;

[0016] Preferably, the multifunctional isocyanate comprises one or more combinations of toluene diisocyanate, diphenylmethane diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate, and the polyol comprises one or a combination of polytetramethylene ether glycol, diethylene glycol, butanediol, homopolymers and / or copolymers of ethylene oxide and propylene oxide;

[0017] Further, it includes a buffer layer, wherein the thermal conductivity of the buffer layer is between 0.06W / (m·K) and 0.09W / (m·K);

[0018] Furthermore, the ratio of the thermal conductivity of the polishing layer to that of the buffer layer is between 0.5 and 1.2.

[0019] A second aspect of the present invention provides a polishing pad, the polishing pad comprising a polishing layer, a buffer layer, an adhesive layer and a back adhesive layer, the thermal conductivity of the polishing pad being between 0.04 W / (m·K) and 0.09 W / (m·K);

[0020] Furthermore, the polishing layer is a closed-cell elastomer formed by a polyurethane substrate with continuous pore separation, the thermal conductivity of the polishing layer is between 0.04W / (m·K) and 0.075W / (m·K), the ratio of the density SG1 of the polishing layer at any point along the diameter direction to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.096, the surface of the polishing layer is engraved with grooves, and the groove shapes include: one or more combinations of concentric grooves, radial grooves, arc grooves, XY grid grooves, and dot matrix punching grooves, and the difference between the volume V0 of the polishing layer before groove engraving and the volume V after groove engraving and the ratio of the volume V0 of the polishing layer before groove engraving (V0-V) / V0 are between 0.02 and 0.19.

[0021] The third and fourth aspects of the present invention provide a method for manufacturing a semiconductor device, comprising a step of grinding the surface of a semiconductor device wafer using a polishing pad, wherein the polishing pad is the polishing pad described in the first and second aspects above.

[0022] Beneficial effects: By controlling the thermal conductivity of the polishing layer, the ratio of the density of any point along the diameter direction of the polishing layer to the minimum density of the polishing layer along the diameter direction, and the difference between the volume of the polishing layer before grooving and the volume after grooving and the ratio of the volume of the polishing layer before grooving within a certain range, the polishing pad prepared by the present invention has lower grinding rate non-uniformity, lower defects, and higher comprehensive polishing performance; and by controlling the thermal conductivity of the buffer layer and the ratio of the thermal conductivity of the polishing layer to the thermal conductivity of the buffer layer within a certain range, and when used in combination with the polishing layer in the present application, the comprehensive polishing performance can be further improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0024] Figure 1 A schematic diagram of a polishing operation process performed by a polishing pad according to an embodiment of the present invention;

[0025] Figure 2 A schematic diagram of a polishing pad provided for an embodiment of the present invention;

[0026] Figure 3 A schematic diagram of sampling the density of each point along the diameter direction of the polishing pad for testing in the present invention;

[0027] Figure 4 A schematic diagram of concentric circular grooves in an embodiment of the present invention;

[0028] Figure 5 A schematic diagram of a concentric circle and radial line composite groove in an embodiment of the present invention;

[0029] Figure 6 A schematic diagram of an XY grid groove in an embodiment of the present invention;

[0030] Figure 7 is a schematic diagram of an arc-shaped groove in an embodiment of the present invention;

[0031] Figure 8 A schematic diagram of a dot matrix perforated groove in an embodiment of the present invention;

[0032] Fig. 9 A schematic diagram of an arc-shaped groove in a comparative example of the present invention;

[0033] Fig.10 A schematic diagram of an XY grid groove in a comparative example of the present invention;

[0034] Fig.11 It is a schematic diagram of an XY grid groove with an included angle in a comparative example of the present invention.

[0035] 1- material to be polished; 2- polishing pad; 3- polishing machine; 4- bracket; 5- polishing liquid; 20- polishing layer; 22- buffer layer; 21- adhesive layer; 23- back adhesive layer. DETAILED DESCRIPTION

[0036] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the invention. If no specific conditions are specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0037] <Method for manufacturing semiconductor device>

[0038] Semiconductor devices are manufactured through a process of polishing the surface of a semiconductor wafer using a polishing pad. A semiconductor wafer generally refers to a wafer with wiring metal and an oxide film stacked on a silicon wafer. The manufacturing method of a semiconductor device of the present invention includes a process of polishing the surface of a semiconductor wafer using a polishing pad, and there is no special restriction on the polishing device.

[0039] For example, using Figure 1The polishing device shown in the figure is carried out, and the polishing device has a polishing machine table 3 supporting a polishing pad 2, a support 4 supporting a material to be polished-a semiconductor wafer 1 and a backing material for uniformly pressurizing the wafer, and a supply mechanism for a polishing liquid 5. The polishing pad 2 is mounted on the polishing machine table 3, for example, by adhering a backing layer. The polishing machine table 3 and the support 4 are configured so that the polishing pad 2 and the semiconductor wafer 1 supported by each are opposite to each other, and each has a rotation axis. In addition, a pressurizing mechanism for pressing the semiconductor wafer 1 onto the polishing pad 2 is provided on one side of the support 4. When polishing, the polishing machine table 3 and the support 4 are rotated, and the semiconductor wafer 1 is pressed onto the polishing pad 2, and polishing is performed while supplying slurry. There are no special restrictions on the flow rate of the slurry, the polishing load, the rotation speed of the polishing machine table, and the rotation speed of the wafer, and they can be adjusted appropriately.

[0040] Thus, the protruding parts of the surface of the semiconductor wafer 1 are removed and polished to a flat state. Thereafter, semiconductor devices are manufactured by dicing, bonding, packaging, etc., and the semiconductor devices are used in arithmetic processing devices, storage devices, etc.

[0041] <Polishing layer>

[0042] Thermal conductivity

[0043] The polishing layer in the embodiment of the present invention is a closed-cell elastomer formed by a polyurethane substrate having continuous pore separation, and the thermal conductivity is between 0.04W / (m·K) and 0.075W / (m·K).

[0044] Preferably, the thermal conductivity of the polishing layer in the present invention is between 0.048 W / (m·K) and 0.065 W / (m·K);

[0045] By controlling the thermal conductivity of the polishing layer, the heat transfer of the polishing layer during the polishing process can be regulated to achieve better polishing performance.

[0046] Density uniformity

[0047] In the embodiment of the present invention, the ratio of the density SG1 of the polishing layer at any point along the diameter direction to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.096 (the density SG1 at any point along the diameter direction does not include the minimum density SG0). Due to the uneven heat dissipation of the polyurethane substrate during the casting and curing process, the density in the radial direction may be uneven. Through research, the present invention has found that by controlling the formula, the ratio of the density at any point along the diameter direction of the polishing layer to the minimum density in the radial direction can be controlled within a certain range, so that good polishing performance can be obtained.

[0048] The method for measuring the radial density of the polishing layer in the embodiment of the present invention can be selected by using a conventional test method in the art. As an example of a radial test method, the polishing layer can be punched into test samples of a certain size and shape at a certain distance along the radial direction of the polishing layer. The shape of the test sample can be any shape. In the present invention, a circular or square shape is preferably used. Particularly preferably, Figure 3 The shape of the test sample shown is a square, the size of the test sample can be any size, the sampling quantity of the test sample can be determined according to the size of the test sample, and the sampling quantity can be one of 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, and 30. Preferably, an odd number of sampling quantities can be selected.

[0049] In the embodiment of the present invention, the density values ​​of multiple test samples in the radial direction of the polishing layer are tested to reflect the difference in radial density of the polishing layer, and the minimum density SG0 is selected as the denominator, and the density SG1 of other test samples is selected as the numerator, and the ratio of the two is controlled to be between 1.002 and 1.096. Preferably, when the ratio of the two is controlled to be between 1.002 and 1.075, the uniformity of the radial density of the polishing layer can be controlled to obtain an excellent polishing effect.

[0050] Grooves

[0051] In an embodiment of the present invention, the polishing layer may be provided with grooves according to the conventional art, and the grooves are used to receive the polishing liquid during the polishing process. The grooves can be obtained by processing after the polishing pad is formed. The arrangement of the grooves can ensure the smooth discharge and flow of the polishing liquid used in the polishing process. Preferably, the grooves are one or more combinations of concentric grooves, radial grooves, XY grid grooves, arc grooves, lattice perforated grooves, spiral grooves, and hexagonal grooves. Particularly preferably, the grooves are one or more combinations of concentric grooves, radial grooves, XY grid grooves, arc grooves, and lattice perforated grooves. The cross-section of the groove is one or more of a straight sidewall rectangle, a "V" shape, a "U" shape, and a sawtooth shape. Preferably, the cross-section of the groove is a straight sidewall rectangle.

[0052] The groove volume of the polishing layer can be recorded as: the difference between the volume V0 of the polishing layer before grooving and the volume V after grooving; when the ratio of the volume V0 of the polishing layer before grooving to the volume V0 of the polishing layer before grooving is between 0.02 and 0.19, the polishing pad exhibits a higher removal rate and lower defects. In the present invention, preferably, (V0-V) / V0 is between 0.02 and 0.145.

[0053] The volume V0 of the polishing layer before grooving and the volume V after grooving in the embodiment of the present invention can be obtained by conventional methods in the art without special limitation. They can be obtained by calculation based on the actual parameters of the grooves, or by fitting with conventional design software in the art.

[0054] The present invention has found that by simultaneously controlling the thermal conductivity, density uniformity, specific groove shape and groove volume of the polishing layer within a certain range, the polishing pad prepared exhibits excellent comprehensive polishing performance.

[0055] The density of the polishing layer in the embodiment of the present invention is between 0.4 g / cm 3 ~0.73g / cm 3 The tensile strength of the polishing layer is between 2MPa and 18MPa.

[0056] Preferably, the density of the polishing layer in the present invention is between 0.5 g / cm 3 ~0.65g / cm 3 between;

[0057] Preferably, the tensile strength of various polishing layers of the present invention is between 7MPa and 14.5MPa;

[0058] As a preferred solution, when the thermal conductivity, density uniformity and groove volume of the polishing layer are controlled within a certain range, the density is controlled within a lower range, that is, the density is less than 0.65 g / cm 3 When the polishing pad is prepared, the comprehensive polishing performance will be further improved; in the embodiment of the present invention, the comprehensive polishing performance depends on the grinding rate uniformity (NU) and the number of defects. By maintaining a low grinding rate uniformity (NU) and a low number of defects, a higher comprehensive polishing performance can be obtained.

[0059] In the embodiment of the present invention, the polishing layer comprises a polyurethane substrate, and the polyurethane substrate is obtained by reacting a multifunctional isocyanate, a polyol and a curing agent.

[0060] Multifunctional isocyanate

[0061] In the embodiment of the present invention, the polyfunctional isocyanate includes but is not limited to one or more combinations of aromatic isocyanates or aliphatic isocyanates. It is preferred to use more than 80 mol % of aromatic isocyanates, more preferably more than 95 mol % of aromatic isocyanates, and particularly preferably 100 mol % of aromatic isocyanates.

[0062] The aromatic isocyanate includes one or more combinations of toluene diisocyanate, diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, and m-xylylene diisocyanate.

[0063] The aliphatic isocyanate includes one or more combinations of ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate.

[0064] In the embodiment of the present invention, in consideration of the reaction activity and the physical properties of the polishing pad, one or more combinations of toluene diisocyanate, diphenylmethane diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate are preferably used.

[0065] In the embodiments of the present invention, considering the reaction activity and the physical properties of the polishing pad, it is particularly preferred to use one of toluene diisocyanate and 4,4-dicyclohexylmethane diisocyanate or a combination of the two.

[0066] Polyols

[0067] In the embodiment of the present invention, the polyol may include a high molecular weight diol based on polyether, wherein the high molecular weight diol based on polyether includes but is not limited to polytetramethylene ether glycol (PTMEG), polyethylene glycol (PEG), polypropylene glycol (PPG) and one or more combinations of polytetramethylene ether glycol-polyethylene glycol, polytetramethylene ether glycol-polypropylene glycol, polyethylene glycol-polypropylene glycol, homopolymers and / or copolymers of ethylene oxide and propylene oxide, or a high molecular weight polyol formed by homopolymerization or copolymerization of ethylene glycol, propylene glycol, butanediol or an initiator having two hydroxyl groups with the above three small molecule diols, or a variety of combinations.

[0068] In the embodiment of the present invention, the polyol may include a small molecule diol, wherein the small molecule includes but is not limited to one or more combinations of ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, and 1,4-cyclohexanedimethanol.

[0069] In the embodiment of the present invention, the polyol composition may further include a polyester-based polyol, wherein the polyester-based polyol is obtained by a condensation reaction of a diol or a diol / phenol with a dibasic acid, wherein the diol includes ethylene glycol, 1,3-butanediol, 1,4-butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, or one or more combinations thereof. Preferably, the diol includes 1,4-butanediol, one or a combination of hexanediol; the diol / phenol is one or a combination of hydroquinone, resorcinol, naphthalene diol, bisphenol A, bisphenol S, terephthalic acid, isophthalic acid, o-phthalic acid, 2,5-furan dimethanol, terephthalic acid or diphenyl ether diphenol. Preferably, the diol / phenol is one or a combination of hydroquinone and terephthalic acid; the dibasic acid is one or a combination of succinic acid, adipic acid, azelaic acid and sebacic acid.

[0070] In the embodiment of the present invention, considering the reactivity and physical properties of the polishing pad, one or more combinations of polytetramethylene ether glycol (PTMEG), diethylene glycol, butanediol or homopolymers and / or copolymers of ethylene oxide and propylene oxide are preferably used.

[0071] In the embodiments of the present invention, considering the reactivity and physical properties of the polishing pad, it is particularly preferred to use one of polytetramethylene ether glycol (PTMEG) and diethylene glycol or a combination of the two.

[0072] Curing agent

[0073] In the embodiment of the present invention, the curing agent is selected from one or more combinations of aromatic bifunctional curing agents or polyol curing agents. The present invention has no particular limitation on the aromatic bifunctional curing agent or polyol curing agent, and it can be any suitable aromatic bifunctional curing agent or polyol curing agent in the art.

[0074] Examples of aromatic bifunctional curing agents that can be used in embodiments of the present invention include diethyltoluenediamine (DETDA), N,N'-dialkyldiaminodiphenylmethane, 3,5-diethyl-2,4-toluenediamine and its isomers (e.g., 3,5-diethyl-2,6-toluenediamine), 3,5-dimethylthio-2,4-toluenediamine and its isomers, 4,4'-methylene-bis-(2-chloroaniline) (MOCA), 4,4'-bis-(sec-butylamino)-diphenylmethane, 1,4-bis-(sec-butylamino)-benzene, 4,4'-methylene-bis-(2-chloroaniline), 4,4'-dimethylthio-2,4-toluenediamine and its isomers. -methylene-bis-(3-chloro-2,6-diethylaniline) (M-CDEA), polyoxytetramethylene-di-p-aminobenzoate; p,p'-methylenedianiline (MDA); metaphenylenediamine (MPDA); 4,4'-methylene-bis-(2,6-diethylaniline) (MDEA), 4,4'-methylene-bis-(2,3-dichloroaniline) (MDCA), 4,4'-diamino-3,3'-diethyl-5,5'-dimethyldiphenylmethane, 2,2',3,3'-tetrachlorodiaminodiphenylmethane, propylene glycol-di-p-aminobenzoate or one or more combinations thereof.

[0075] Preferably, the aromatic bifunctional curing agent comprises two or more combinations of 4,4'-methylene-bis-(2-chloroaniline) (MOCA), 4,4'-bis-(sec-butylamino)-diphenylmethane, 4,4'-methylene-bis-(3-chloro-2,6-diethylaniline) (M-CDEA), and polyoxytetramethylene-di-p-aminobenzoate. Considering the unique chemical structure of MOCA, in order to ensure that the polishing pad has a suitable operating time in the preparation, and the obtained polishing pad has good polishing performance, therefore, preferably, the aromatic bifunctional curing agent comprises one or a combination of 4,4'-methylene-bis-(2-chloroaniline) (MOCA) and 4,4'-methylene-bis-(3-chloro-2,6-diethylaniline) (M-CDEA); particularly preferably, the aromatic bifunctional curing agent comprises 4,4'-methylene-bis-(2-chloroaniline) (MOCA).

[0076] The polyurethane substrate in the embodiment of the present invention can be manufactured by using a well-known polyurethane forming technology such as a melt method and a solution method, and can also be manufactured by any conventional method such as a prepolymer method and a one-shot injection method. The prepolymer method is to first synthesize an isocyanate-terminated prepolymer from a multifunctional isocyanate and a polyol composition component and react it with a polyamine composition; the one-shot injection method is to react a multifunctional isocyanate, a polyol composition and a polyamine composition in one step; in the present invention, the prepolymer method is preferably used to synthesize the polyurethane substrate.

[0077] The isocyanate-terminated prepolymer can be obtained by reacting the multifunctional isocyanate with the polyol composition, or by purchasing a commercially available prepolymer product.

[0078] Commercially available isocyanate-terminated prepolymers include, but are not limited to, any one or more combinations of the series of prepolymers produced by Chemtura: LF800A, LF900A, LF910A, LF930A, LF931A, LF939A, LF950A, LF952A, LF600D, LF601D, LF650D, L42, L325, L100, L150, L167, L200, L275, L300, L310, L367, L480, L500, LF667D, LF700D, LF750D, LF751D, LF752D, LF753D, LFG963A, LFG964A, and LFG740D.

[0079] Hollow microsphere polymer

[0080] In the process of preparing the polishing layer, the hollow microsphere polymer is usually evenly dispersed in the polishing layer, so as to adjust the polishing effect of the polishing layer.

[0081] The term "hollow microsphere polymer" in the embodiments of the present invention refers to an expandable hollow polymer microsphere that can moderately expand during the curing process by virtue of the temperature increase caused by the reaction exotherm. The polishing performance of the polishing layer can be further adjusted by adjusting the distribution mode (such as density) of the hollow microsphere polymer in the polyurethane polishing layer and adjusting the particle size of the hollow microsphere polymer. Preferably, the hollow microsphere polymer is dispersed in the polishing layer so that the final porosity of the polishing layer is 10% to 65%.

[0082] Preferably, the hollow microsphere polymer includes but is not limited to a vesicular structure having an outer wall of polyacrylonitrile and polyacrylonitrile copolymer, and can be purchased from microspheres or microbeads of any company of Akzo Nobel, Matsumoto Oil & Fat Pharmaceutical Co., Ltd. or Sekisui Chemical Co., Ltd. Particularly preferably, in the embodiment of the present invention, Akzo Nobel hollow microspheres or Matsumoto microbeads F series are selected.

[0083] <Buffer layer>

[0084] In an embodiment of the present invention, a buffer layer is provided on the back of the polishing layer. The buffer layer can reduce the impact applied to the polishing pad during the polishing process. The elastic modulus of the buffer layer is higher than that of the polishing layer. The buffer layer is a necessary layer to take into account both planarity and uniformity in a trade-off relationship in CMP. Planarity refers to the flatness of the polished pattern portion of the polished material having tiny bumps and depressions generated when the pattern is formed, and uniformity refers to the uniformity of the entire polished material. The planarity is improved by the characteristics of the polishing layer, and the uniformity is improved by the characteristics of the buffer layer.

[0085] In the embodiment of the present invention, the thermal conductivity of the buffer layer is between 0.06 W / (m·K) and 0.09 W / (m·K).

[0086] It is found in the examples of the present invention that when the ratio of the thermal conductivity of the polishing layer to the buffer layer is within a certain range, the polishing pad exhibits good polishing performance. Preferably, the ratio of the polishing layer to the buffer layer is between 0.5 and 1.2.

[0087] In the embodiment of the present invention, the buffer layer has a thickness of 30 mil to 150 mil.

[0088] In the embodiment of the present invention, the buffer layer is a non-woven fabric coated with an impregnated material or a foamed resin, wherein the non-woven fabric coated with an impregnated material comprises a non-woven fabric impregnated with polyurethane, wherein the non-woven fabric impregnated with polyurethane is composed of a fiber non-woven fabric such as a polyester non-woven fabric, a nylon non-woven fabric, an acrylic non-woven fabric, and a polyurethane resin: wherein the foaming resin comprises commonly used foaming resins such as polyurethane, polyethylene, polypropylene, polysulfone, polyvinyl chloride, and silicone resin. The preferred buffer layer is one of the non-woven fabric impregnated with polyurethane or a polyurethane foaming resin or a polypropylene foaming resin in the non-woven fabric coated with an impregnated material.

[0089] <Polishing pad>

[0090] The polishing pad in the embodiment of the present invention is as follows Figure 2 As shown, it includes a polishing layer 20, a buffer layer 22, an adhesive layer 21 and a back adhesive layer 23. The polishing pad in the present invention is arranged from top to bottom as a polishing layer 20, an adhesive layer 21, a buffer layer 22, and a back adhesive layer 23, wherein the adhesive layer 21 is used for bonding the polishing layer 20 and the buffer layer 22, and the back adhesive layer 23 also includes a release film or a release paper. When in use, the release film or the release paper can be torn off to achieve the bonding of the polishing pad and the polishing machine.

[0091] In the present invention, excellent polishing performance is taken into consideration. When the thermal conductivity of the polishing pad in the embodiment of the present invention is controlled to be between 0.04W / (m·K) and 0.09W / (m·K), preferably, when the thermal conductivity of the polishing pad in the embodiment of the present invention is controlled to be between 0.045W / (m·K) and 0.083W / (m·K), the polishing pad exhibits excellent comprehensive polishing performance. The polishing pad may be composed of the polishing layer and buffer layer of the present invention, or a polishing layer and buffer layer composition known in the art.

[0092] Example

[0093] The present invention is further described below with reference to the schematic examples shown in the accompanying drawings. Through the following description, various advantages of the present invention will become more obvious. The same figure marks in the accompanying drawings refer to the same parts. The shapes and sizes of the components in the schematic drawings are only for illustration and cannot be recognized as reflecting the actual shape, size and absolute position.

[0094] Throughout the specification, unless otherwise specified, the terms used herein should be understood as the meanings commonly used in the art. Therefore, unless otherwise specified, all technical and scientific terms used herein have the same meanings as those generally understood by technicians of the present invention. If there is any conflict, the present specification takes precedence.

[0095] TDI: toluene diisocyanate;

[0096] HMDI: 4,4'-dicyclohexylmethane diisocyanate;

[0097] PTMEG: polytetramethylene ether glycol;

[0098] PPG: copolymer of ethylene oxide and propylene oxide;

[0099] MDI: diphenylmethane diisocyanate;

[0100] DEG: diethylene glycol;

[0101] MOCA: 4,4'-methylene-bis-(2-chloroaniline);

[0102] M-CDEA: 4,4'-methylene-bis-(3-chloro-2,6-diethylaniline);

[0103] Hollow polymer microspheres: 551DE40d42, average particle size 40μm, density 0.042g / cm 3 , 461DE20d70, average particle size 20μm, density 0.07g / cm 3 .

[0104] The above raw materials are all from bulk industrial products on the market, and manufacturers include BASF, Covestro, Wanhua Chemical, Suzhou Xiangyuan, Chizhou Tianci, Mitsui Chemicals, Mitsubishi Chemical, etc.

[0105] The following physical and chemical parameter determination methods and other parameter calculation methods are as follows:

[0106] Density of polishing layer

[0107] Calculate according to the following formula: SG = m / v = m / (π(d / 2)^2*h), where m is the weight of the polishing layer, d is the diameter of the polishing layer, and h is the thickness of the polishing layer.

[0108] Polishing layer / buffer layer / polishing pad thermal conductivity

[0109] Polishing layer sample preparation: Cut the polishing layer into thin slices with a thickness of 0.8 mm, or use a grinder to remove the uneven glue layer and concave grooves from the grooved polishing layer, and grind it into a uniform thickness of about 0.8 mm. Then use a circular die cutter with a diameter of 4 cm to cut it to obtain a polishing layer test sample with a diameter of 4 cm and a thickness of 0.8 mm.

[0110] Buffer layer sample preparation: The original buffer layer sample is directly cut with a die cutter with a diameter of 4 cm to obtain a buffer layer test sample with original thickness and a diameter of 4 cm.

[0111] Polishing pad sample preparation: Grind the grooves of the finished polishing pad with a grinder until the polishing layer thickness is about 0.8 cm, or use pressure-sensitive adhesive or hot-melt adhesive to bond the polishing layer and the buffer layer, and then stick the backing adhesive on one side of the buffer layer.

[0112] Use a DRL-Ⅲ thermal conductivity meter and a low-temperature constant temperature circulator, set the circulating refrigeration temperature to 5°C, take the polishing layer / buffer layer / polishing pad test sample before testing, and evenly apply thermal grease on both sides of the test sample. Set the pressure to 50N, the test temperature to 50°C, and the safety temperature to 340°C.

[0113] Tensile strength of polishing layer

[0114] National standard, use electronic vernier caliper and electronic universal testing machine for measurement.

[0115] Radial density uniformity of polishing layer

[0116] like Figure 3 As shown, 15 square samples Y1~Y15 are taken on the diameter of the polishing layer, and SG=m / v=m1 / (L^2*h) are calculated respectively, where m1 is the weight of the square sample Y1~Y15, L is the side length of the square sample Y1~Y15, and h is the thickness of the polishing layer; and SG0 is the point with the lowest density among the 15 samples.

[0117] Polishing layer groove volume

[0118] The difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 were calculated after simulating the polishing layer using SolidWorks 3D design software.

[0119] Shore hardness of polishing layer

[0120] Use REX digital display Shaw D automatic hardness tester and Bareiss digital display Shaw D automatic hardness tester for measurement. Punch the sample to be tested into 3"×3" square specimens. The thickness of the sample to be tested is not less than 5mm. The measuring point is at least 9mm away from any edge of the sample. The hardness value on the same sample is measured at least 6mm apart and the maximum value is taken. The sample needs to be tested under a standard environment of 23±2℃ and humidity 50%±10%.

[0121] Polishing performance evaluation of polishing pads

[0122] The polishing pads prepared in the examples and comparative examples were tested on a machine to evaluate the polishing performance. The test conditions were as follows:

[0123] The test machine is AMAT Refelxion (Modify 5Zone);

[0124] The polishing liquid was ANJI U3061A (slurry (g): DIW (g): 30% H2O2 (g) = 1: 10: 0.37), with a flow rate of 300 mL / min;

[0125] The dressing disk is Saesol Disk AJ27, 6lbf, in-situ 100%; Platen / Head Speed ​​= 97 / 91;

[0126] Zone Pressure: RR / Z1 / Z2 / Z3 / Z4 / Z5:5.90 / 5.10 / 2.40 / 2.15 / 2.10 / 2.20;

[0127] The wafer used is Pattern wafer: Semitech 754, Cu Blanket wafer PreThickness 10~12KA.

[0128] The change of removal rate during polishing was recorded, the data of 0 / 5hrs / 10hrs / 15hrs / 20hrs were recorded, and the change of polishing rate non-uniformity (NU) of 0 / 5hrs / 10hrs / 15hrs / 20hrs was recorded and the average value was calculated using a four-probe film thickness meter (NAPSON Crestest / RG3000).

[0129] Defect evaluation

[0130] The defects on the polished substrate after polishing are obtained using KLA-Tencor The SP2 defect inspection system is used for inspection, and the defect size is: 0.16μm; ○○ indicates almost no defect, ○ indicates very few defects, × indicates a few defects, ×× indicates a relatively large number of defects, and ××× indicates a large number of defects.

[0131] Example 1-1

[0132] This embodiment provides a polishing pad, and the preparation method thereof is as follows:

[0133] Step 1: Take 32.52 parts by mass of TDI, 8 parts by mass of HMDI, 53.78 parts by mass of PTMEG1000 and 5.7 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat it to 25-65°C, and degas it under vacuum (-0.095MPa) for 2 hours to remove the gas and small molecular compounds in the prepolymer; then add 8.99 parts by mass of hollow microsphere polymer 551DE40d42 with an average particle size of 40μm, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas it again under vacuum (-0.095MPa) for 2 hours, and set aside.

[0134] Step 2: Heat 25.54 parts by mass of MOCA to 115° C. for standby use.

[0135] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, let it cool down to room temperature in the oven automatically, and then cut into 80 mil thick sheets, a total of 60 sheets.

[0136] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the center blank area diameter is 2 inches. After grooving, it becomes a polishing layer.

[0137] Step 5: Use double-sided tape for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P1-1, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).

[0138] Example 1-2

[0139] This embodiment provides a polishing pad P1-2, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 32.3 parts by mass of TDI and 7.84 parts by mass of HMDI, 54.21 parts by mass of PTMEG1000 and 5.65 parts by mass of DEG; the hollow microsphere polymer is 6.76 parts by mass of 551DE40d42 with an average particle size of 40 μm; 25.11 parts by mass of MOCA is selected as the curing agent; and the rest is the same as Example 1-1.

[0140] Examples 1-3

[0141] This embodiment provides a polishing pad P1-3, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 39.01 parts by mass of TDI, 55.08 parts by mass of PTMEG1000 and 5.91 parts by mass of DEG; the hollow microsphere polymer is 6.08 parts by mass of 551DE40d42 with an average particle size of 40 μm; the curing agent is selected to use 26.35 parts by mass of MOCA, and the rest is the same as Example 1-1.

[0142] Examples 1-4

[0143] This embodiment provides a polishing pad P1-4, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 31.48 parts by mass of TDI and 7.63 parts by mass of HMDI, 55.88 parts by mass of PTMEG1000 and 5.01 parts by mass of DEG; the hollow microsphere polymer is 9.47 parts by mass of 461DE20d70 with an average particle size of 20 μm; 24.85 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 1-1.

[0144] Examples 1-5

[0145] This embodiment provides a polishing pad P1-5, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 38.84 parts by mass of TDI, 55.29 parts by mass of PTMEG1000 and 5.87 parts by mass of DEG; the hollow microsphere polymer is 7.57 parts by mass of 461DE20d70 with an average particle size of 20 μm; 26.16 parts by mass of MOCA are selected as the curing agent, and the rest is the same as Example 1-1.

[0146] Examples 1-6

[0147] This embodiment provides a polishing pad P1-6, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 25.67 parts by mass of TDI and 5.42 parts by mass of HMDI, 65.30 parts by mass of PTMEG1400 and 3.61 parts by mass of DEG; the hollow microsphere polymer is 6.62 parts by mass of 461DE20d70 with an average particle size of 20 μm; 28.88 parts by mass of M-CDEA is selected as the curing agent, and the rest is the same as Example 1-1.

[0148] Examples 1-7

[0149] This embodiment provides a polishing pad P1-7, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 31.97 parts by mass of TDI, 4.22 parts by mass of HMDI and 63.81 parts by mass of PTMEG650; the hollow microsphere polymer is 2.87 parts by mass of 551DE40d42 with an average particle size of 40 μm; and 23.63 parts by mass of MOCA is selected as the curing agent. The rest is the same as Example 1-1.

[0150] Examples 1-8

[0151] This embodiment provides a polishing pad P1-8, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 34.31 parts by mass of MDI and 65.69 parts by mass of PPG (Bluestar Dongda polyether polyol product MN-3050D); the hollow microsphere polymer is 2.6 parts by mass of 551DE40d42 with an average particle size of 40 μm; the curing agent is selected to use 23.11 parts by mass of low molecular weight diol (Dai Nippon Ink PANDEX TM-228), and the rest is the same as Example 1-1.

[0152] Examples 1-9

[0153] This embodiment provides a polishing pad, and the preparation method thereof is as follows:

[0154] Step 1: Take 37.72 parts by mass of TDI, 56.84 parts by mass of PTMEG1000 and 5.44 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat it to 25-65°C, and degas it under vacuum (-0.095MPa) for 2 hours to remove the gas and small molecular compounds in the prepolymer; then add 5.59 parts by mass of hollow microsphere polymer 551DE40d42 with an average particle size of 40μm, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas it again under vacuum (-0.095MPa) for 2 hours, and set aside.

[0155] Step 2: Heat 25.25 parts by mass of MOCA to 115° C. for standby use.

[0156] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, let it cool down to room temperature in the oven automatically, and then cut into 80 mil thick sheets, a total of 60 sheets.

[0157] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the center blank area diameter is 2 inches. After grooving, it becomes a polishing layer.

[0158] Step 5: Use double-sided tape for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P1-9, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).

[0159] Examples 1-10

[0160] This embodiment provides a polishing pad P1-10, and its preparation method is different from that of Example 1-9 in that: the isocyanate-terminated prepolymer is obtained by reacting 39.83 parts by mass of TDI, 53.86 parts by mass of PTMEG1000 and 6.31 parts by mass of DEG; the hollow microsphere polymer is 4.68 parts by mass of 551DE40d42 with an average particle size of 40 μm; 26.85 parts by mass of MOCA are selected as the curing agent, and the rest is the same as Example 1-9.

[0161] Embodiment 1-11

[0162] This embodiment provides a polishing pad P1-11, and its preparation method is different from that of Example 1-9 in that: the isocyanate-terminated prepolymer is obtained by reacting 38.91 parts by mass of TDI and 1.84 parts by mass of HMDI, 52.84 parts by mass of PTMEG1000 and 6.41 parts by mass of DEG; the hollow microsphere polymer is 8.39 parts by mass of 551DE40d42 with an average particle size of 40 μm; 27.27 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 1-9.

[0163] Examples 1-12

[0164] This embodiment provides a polishing pad P1-12, and its preparation method is different from that of Example 1-9 in that: the isocyanate-terminated prepolymer is obtained by reacting 32.40 parts by mass of TDI and 7.14 parts by mass of HMDI, 55.01 parts by mass of PTMEG1000 and 5.45 parts by mass of DEG; the hollow microsphere polymer is 6.94 parts by mass of 461DE20d70 with an average particle size of 20 μm; 24.88 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 1-9.

[0165] Examples 1-13

[0166] This embodiment provides a polishing pad, and the preparation method thereof is as follows:

[0167] Step 1: Take 38.84 parts by mass of TDI, 55.29 parts by mass of PTMEG1000 and 5.87 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat it to 25-65°C, and degas it under vacuum (-0.095MPa) for 2 hours to remove the gas and small molecular compounds in the prepolymer; then add 7.57 parts by mass of hollow microsphere polymer 551DE40d42 with an average particle size of 40μm, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas it again under vacuum (-0.095MPa) for 2 hours, and set aside.

[0168] Step 2: Heat 26.16 parts by mass of MOCA to 115° C. for standby use.

[0169] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, let it cool down to room temperature in the oven automatically, and then cut into 80 mil thick sheets, a total of 60 sheets.

[0170] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30.5 mil, groove width 20.5 mil, groove spacing 120 mil, center blank area diameter 1 inch, and the polishing layer after grooving. The difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 is 0.081.

[0171] Step 5: Use double-sided tape for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P1-13, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).

[0172] Examples 1-14

[0173] The present embodiment provides a polishing pad P1-14, whose prepolymer and curing agent are the same as those of Embodiment 1-13, except that the groove shape is different. The groove parameters in this embodiment are: the groove shape is a combination of concentric circle grooves and radial line grooves with a blank (ungrooved) area in the center. The concentric circle parameters are: groove depth 30.5 mil, groove width 20.5 mil, groove spacing 120 mil, and center blank area diameter 1 inch; radial line: 8 lines, groove width 78.7 mil, groove depth 32.5 mil, and the polishing layer after grooving, wherein the difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 is 0.088.

[0174] Examples 1-15

[0175] This embodiment provides a polishing pad, and the preparation method thereof is as follows:

[0176] Step 1: Take 31.48 parts by mass of TDI, 7.63 parts by mass of HMDI, 55.88 parts by mass of PTMEG1000 and 5.01 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat it to 25-65°C, and degas it under vacuum (-0.095MPa) for 2 hours to remove the gas and small molecular compounds in the prepolymer; then add 9.47 parts by mass of hollow microsphere polymer 461DE20d70 with an average particle size of 20μm, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas it again under vacuum (-0.095MPa) for 2 hours, and set aside.

[0177] Step 2: Heat 24.85 parts by mass of MOCA to 115° C. for standby use.

[0178] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, let it cool down to room temperature in the oven automatically, and then cut into 80 mil thick sheets, a total of 60 sheets.

[0179] Step 4: The groove selection uses XY grid grooves, and the groove parameters are: groove depth 22.4mil, groove width 80.4mil, groove spacing 1572mil; after grooving, it is the polishing layer, among which, the difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 is 0.02.

[0180] Step 5: Use double-sided tape for the intermediate glue and the back glue layer, use the intermediate glue to bond the above-mentioned polishing layer and the buffer layer, and bond the back glue layer on the other side of the buffer layer (the side not bonded with the polishing layer) to obtain the polishing pad P1-15, wherein the buffer layer uses a polyurethane impregnated non-woven fabric material (SUBA).

[0181] Examples 1-16

[0182] This embodiment provides a polishing pad P1-16, whose prepolymer and curing agent are the same as those in Embodiment 1-15, and the groove is selected to use an arc groove such as Figure 7 As shown, the groove parameters in this embodiment are: groove depth 34.7 mil, groove width 31.2 mil, and the polishing layer is formed after groove carving, wherein the difference between the volume V0 before groove carving and the volume V after groove carving and the ratio of the volume V0 of the polishing layer before groove carving (V0-V) / V0 is 0.19.

[0183] Examples 1-17

[0184] This embodiment provides a polishing pad P1-17, whose prepolymer and curing agent are the same as those of embodiment 1-15, except that the groove shape is different. The groove parameters in this embodiment are: the groove selection uses a dot matrix punching groove such as Figure 8 As shown, the grooving parameters are: hole diameter 67 mil, hole spacing 215 mil, and the polishing layer after grooving. Among them, the difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 is 0.145.

[0185] Comparative Example 1-1

[0186] This embodiment provides a polishing pad PD1-1, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 33.53 parts by mass of TDI, 7.94 parts by mass of HMDI, 52.86 parts by mass of PTMEG1000 and 5.67 parts by mass of DEG; 27.11 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 1-1.

[0187] Comparative Example 1-2

[0188] This embodiment provides a polishing pad PD1-2, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 32.86 parts by mass of TDI, 7.19 parts by mass of HMDI, 54.28 parts by mass of PTMEG1000 and 5.67 parts by mass of DEG; 25.22 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 1-1.

[0189] Comparative Examples 1-3

[0190] This embodiment provides a polishing pad PD1-3, and its preparation method is different from that of Example 1-9 in that: the isocyanate-terminated prepolymer is obtained by reacting 36.14 parts by mass of TDI, 59.17 parts by mass of PTMEG1000 and 4.69 parts by mass of DEG; the hollow microsphere polymer is 9.68 parts by mass of 551DE40d42 with an average particle size of 40 μm; the curing agent is selected to use 24.24 parts by mass of MOCA, and the rest is the same as Example 1-9.

[0191] Comparative Examples 1-4

[0192] This comparative example provides a polishing pad PD1-4, whose prepolymer and curing agent are the same as those of Examples 1-4, except that the groove shape is different. The groove parameters in this example are: the groove is selected to use an arc groove such as Fig. 9 As shown, the groove parameters are: groove depth 35.5 mil, groove width 32.6 mil, and the polishing layer after grooving. Among them, the difference between the volume V0 before grooving and the volume V after grooving and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 is 0.203.

[0193] Comparative Examples 1-5

[0194] This comparative example provides a polishing pad PD1-5, whose prepolymer and curing agent are the same as those of Examples 1-4, except that the groove shape is different. The groove parameters in this example are: the groove selection uses an XY grid groove such as Fig.10As shown, the groove parameters are: groove depth 23.5 mil, groove width 84.1 mil, groove spacing 2868 mil; after groove carving, there is a polishing layer, wherein the difference between the volume V0 before groove carving and the volume V after groove carving and the ratio of the volume V0 of the polishing layer before groove carving (V0-V) / V0 is 0.015.

[0195] Comparative Examples 1-6

[0196] This comparative example provides a polishing pad PD1-6, whose prepolymer and curing agent are the same as those of Examples 1-4, except that the groove shape is different. The groove parameters in this example are: the groove selection uses an XY grid groove such as Fig.11 As shown in the figure, the groove parameters are: groove depth 24mil, groove width 85.5mil, groove spacing 3014mil, and the angle between horizontal and vertical grid lines is 30°; after groove carving, there is a polishing layer, wherein the difference between the volume V0 before groove carving and the volume V after groove carving and the ratio of the volume V0 of the polishing layer before groove carving (V0-V) / V0 is 0.013.

[0197] Comparative Examples 1-7

[0198] This embodiment provides a polishing pad PD1-7, and its preparation method is different from that of Example 1-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 39.21 parts by mass of TDI, 54.85 parts by mass of PTMEG1000 and 5.94 parts by mass of DEG; the hollow microsphere polymer is 0.93 parts by mass of 551DE40d42 with an average particle size of 40 μm; the curing agent is selected to use 26.60 parts by mass of MOCA, and the rest is the same as Example 1-1.

[0199] Among them, in Examples 1-1 to 1-13, the groove shapes are all concentric grooves, and the grooving parameters are the same. Therefore, the difference between the volume V0 before grooving and the volume V after grooving in Examples 1-1 to 1-13 and the ratio of the volume V0 of the polishing layer before grooving (V0-V) / V0 are both 0.081.

[0200] The ratio of the density SG1 of the polishing layer at any point along the diameter direction and the minimum density SG0 of the polishing layer along the diameter direction involved in Examples 1-1 to 1-17 and Comparative Examples 1-1 to 1-7 is shown in Table 1, where "-" represents the minimum point itself; the physical parameters of the polishing layer involved in Examples 1-1 to 1-17 and Comparative Examples 1-1 to 1-7 and the corresponding performance indicators of the polishing pads P1-1 to P1-17 and PD1-1 to PD1-7 are shown in Table 2.

[0201] Table 1

[0202]

[0203] Table 2

[0204]

[0205] The thermal conductivity, the ratio of the density SG1 of the polishing layer at any point along the diameter direction to the minimum density SG0 of the polishing layer along the diameter direction, the difference between the volume V0 of the polishing layer before grooving and the volume V after grooving, and the ratio of the volume V0 of the polishing layer before grooving are all within the protection range. The polishing pads prepared in Examples 1-1 to 1-17 show excellent comprehensive polishing performance, especially when the density is lower than 0.73 g / cm 3 , NU is lower and defects are further reduced; the thermal conductivity of the polishing layer involved in Comparative Examples 1-1, 1-2 and 1-7 is higher than the upper limit of the thermal conductivity in the present application. The radial density changes of Comparative Examples 1-1 and 1-2 are also lower than the lower limit. Although their grinding rates are comparable, NU and defects are significantly deteriorated. The present application focuses more on the changes in NU and defects. Even if the grinding rates are comparable, such degradation is unacceptable. The thermal conductivity of Comparative Example 1-3 is lower than the lower limit of the thermal conductivity in the present application, and a poor comprehensive polishing performance is also obtained. For the polishing layers involved in Comparative Examples 1-4 to 1-6, their (V0-V) / V0 is greater than or less than 0.19 or 0.02, and they also show poor comprehensive polishing performance.

[0206] Preparation Example 2-1

[0207] 6 parts by mass of TDI and 17.5 parts by mass of MDI were put into a 1L three-necked flask, and the reaction temperature was raised to 70°C within 30 minutes. After TDI and MDI were completely melted, the stirrer was started at a stirring speed of 300 rpm. 57 parts by mass of polyester polyol Kurapol P-2010 and 3.4 parts by mass of polyether polyol PPG3000 were dissolved and then added dropwise to TDI and MDI, and the addition time was controlled within 1.5 hours. After the dropwise addition was completed, 0.005 parts by mass of dibutyltin dilaurate was added, and the reaction was continued at 80°C for 2 hours. The reactants were then degassed, and the vacuum degree of the degassed reaction was controlled to be -0.096 MPa, 80°C, and 60 minutes to obtain a prepolymer with a free -NCO mass content of 7.5%. 6.2 parts by mass of 1,4-butanediol and 47 parts by mass of DMF were added to the prepolymer, mixed evenly, and reacted at 80°C for 200 minutes to obtain the desired polyurethane resin solution. The solvent was then removed to obtain polyurethane resin A1.

[0208] 1. Prepare 30 parts by mass of polyester nonwoven fabric with a density of 0.15 g / cm 3, the fiber fineness is 3d, and the fiber length is 50mm; immersed in a polyurethane resin solution, wherein the polyurethane resin solution selects 15 parts by mass of polyurethane resin A1 as the polyurethane resin and selects 85 parts by mass of DMF as the solvent.

[0209] 2. Soak at 60°C for 300 minutes, then use water for wet coagulation. After coagulation, take out the above materials, wash off the excess solvent in water, and dry at 120°C for 30 minutes. Then you can get the non-woven fabric impregnated with polyurethane, which is the coated and impregnated non-woven fabric.

[0210] The obtained non-woven fabric coated with the resin is polished to a 50 mil thin sheet and then cut into the same shape as the polyurethane polishing layer to obtain the buffer layer S2-1.

[0211] Preparation Example 2-2

[0212] The preparation method of the buffer layer S2-2 is similar to that of Example 2-1, wherein the polyurethane resin A1 is replaced by ESTANE ETE55DT3TPU of ETE series; non-woven fabric is; 31.3 parts by mass of polyester non-woven fabric, wherein the density is 0.21g / cm 3 , fiber fineness is 3d, and fiber length is 50mm.

[0213] Preparation Example 2-3

[0214] The preparation method of the buffer layer S2-3 is similar to that of Example 2-1, wherein the polyurethane resin A1 is replaced by polyurethane resin A1 produced by Lubrizol Corporation. ESTANE ETE50DT3TPU of ETE series; non-woven fabric is; 30 parts by weight of polyester non-woven fabric, wherein the density is 0.33g / cm 3 , fiber fineness is 3d, and fiber length is 50mm.

[0215] Preparation Example 2-4

[0216] The preparation method of the buffer layer S2-4 is similar to that of Example 2-1, wherein the polyurethane resin A1 is replaced by ESTANE ETE50DT4TPU of ETE series; non-woven fabric is; 30 parts by weight of polyester non-woven fabric, wherein the density is 0.42g / cm 3 , fiber fineness is 3d, and fiber length is 50mm.

[0217] Preparation Example 2-5

[0218] 1. Mix 100 parts by mass of LF900A isocyanate-terminated prepolymer and 4.8 parts by mass of SH-192 surfactant at 70°C, heat 16.9 parts by mass of MOCA to 115°C to completely melt it into a clear and transparent liquid, then add it to the mixture of isocyanate-terminated prepolymer and surfactant, install a stirrer and set the speed to 2000 rpm, stir for 10 minutes, and then slowly remove the stirrer.

[0219] 2. The mixed solution was then cast into a cylindrical mold before thickening to form a casting block with a thickness of 12 cm, and gelled at 70°C for 15 minutes, and then the casting body was heated to 80°C within 30 minutes and cured for 16 hours. After curing, it was automatically cooled to room temperature in an oven and then cut into thin sheets with a thickness of 50 mil, which were the buffer layer S2-5.

[0220] Example 2-1

[0221] This embodiment provides a polishing pad, and the preparation method thereof is as follows:

[0222] Step 1: Take 39.01 parts by mass of TDI, 55.08 parts by mass of PTMEG1000 and 5.91 parts by mass of DEG to react to obtain an isocyanate-terminated prepolymer, heat it to 25-65°C, and degas it under vacuum (-0.095MPa) for 2 hours to remove the gas and small molecular compounds in the prepolymer; then add 6.08 parts by mass of hollow microsphere polymer 551DE40d42 with an average particle size of 40μm, stir to make the hollow microsphere polymer uniformly dispersed in the prepolymer, degas it again under vacuum (-0.095MPa) for 2 hours, and set aside.

[0223] Step 2: Heat 26.35 parts by mass of MOCA to 115° C. for standby use.

[0224] Step 3: Mix the prepolymer and curing agent under high-speed shearing, then cast into a round mold to form a casting block with a thickness of 12 cm, let it stand at room temperature for 10 minutes, and then place it in a 100°C oven for curing for 16 hours. After curing, let it cool down to room temperature in the oven automatically, and then cut into 80 mil thick sheets, a total of 60 sheets.

[0225] Step 4: The groove selection uses concentric grooves with a blank (ungrooved) area in the center. The groove parameters are: groove depth 30mil, groove width 20mil, groove spacing 120mil, and the radius of the center blank area is 60-70mm. After grooving, it becomes a polishing layer.

[0226] Step 5: Use double-sided tape for the intermediate adhesive and the back adhesive layer, use the intermediate adhesive to bond the polishing layer and the buffer layer S2-1, and bond the back adhesive layer on the other side of the buffer layer (the side not bonded with the polishing layer), and you can get the polishing pad P2-1.

[0227] Example 2-2

[0228] This embodiment provides a polishing pad P2-2, and steps 1 to 4 in the preparation method thereof are the same as those in embodiment 2-1, except that in step 5, the buffer layer S2-1 is replaced by S2-2.

[0229] Example 2-3

[0230] This embodiment provides a polishing pad P2-3, and its preparation method is different from that of Example 2-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 31.97 parts by mass of TDI, 4.22 parts by mass of HMDI and 63.81 parts by mass of PTMEG650; the hollow microsphere polymer is 2.87 parts by mass of 551DE40d42 with an average particle size of 40 μm; and the curing agent is selected to use 23.63 parts by mass of MOCA, and the rest is the same as Example 2-1.

[0231] Embodiment 2-4

[0232] The present embodiment provides a polishing pad P2-4, and its preparation method is different from that of Example 2-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 32.52 parts by mass of TDI, 8 parts by mass of HMDI, 53.78 parts by mass of PTMEG1000 and 5.7 parts by mass of DEG; the hollow microsphere polymer is 8.99 parts by mass of 551DE40d42 with an average particle size of 40 μm; 25.54 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 2-1; and the buffer layer S2-1 is replaced by S2-2 in step five.

[0233] Embodiment 2-5

[0234] The present embodiment provides a polishing pad P2-5, and its preparation method is different from that of Example 2-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 38.84 parts by mass of TDI, 55.29 parts by mass of PTMEG1000 and 5.87 parts by mass of DEG; the hollow microsphere polymer is 7.57 parts by mass of 461DE20d70 with an average particle size of 20 μm; 26.16 parts by mass of MOCA are selected as the curing agent, and the rest is the same as Example 2-1; and the buffer layer S2-1 is replaced by S2-3 in step five.

[0235] Embodiment 2-6

[0236] The present embodiment provides a polishing pad P2-6, and its preparation method is different from that of Example 2-1 in that: the isocyanate-terminated prepolymer is obtained by reacting 38.84 parts by mass of TDI, 55.29 parts by mass of PTMEG1000 and 5.87 parts by mass of DEG; the hollow microsphere polymer is 7.57 parts by mass of 461DE20d70 with an average particle size of 20 μm; 26.16 parts by mass of MOCA are selected as the curing agent, and the rest is the same as Example 2-1; and the buffer layer S2-1 in step five is replaced by S2-5.

[0237] Comparative Example 2-1

[0238] The present embodiment provides a polishing pad PD2-1, and its preparation method is the same as that of comparative example 1-1, except that: the isocyanate-terminated prepolymer is obtained by reacting 33.53 parts by mass of TDI, 7.94 parts by mass of HMDI, 52.86 parts by mass of PTMEG1000 and 5.67 parts by mass of DEG; 27.11 parts by mass of MOCA is selected as the curing agent, and the rest is the same as that of Example 2-1.

[0239] Comparative Example 2-2

[0240] The present embodiment provides a polishing pad PD2-2, and its preparation method is the same as that of Example 1-1, except that: the isocyanate-terminated prepolymer is obtained by reacting 32.52 parts by mass of TDI and 8 parts by mass of HMDI, 53.78 parts by mass of PTMEG1000 and 5.70 parts by mass of DEG; the hollow microsphere polymer is 8.99 parts by mass of 551DE40d42 with an average particle size of 40 μm; 25.54 parts by mass of MOCA is selected as the curing agent, and the rest is the same as Example 2-1.

[0241] The physical properties of the polishing layers involved in Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-2, the physical properties of the buffer layers in Preparation Examples 2-1 to 2-5, and the corresponding performance indicators of the polishing pads P2-1 to P2-6 and PD2-1 to PD2-2 are shown in Table 3.

[0242] The thermal conductivities of the polishing pads P2-1 to P2-6 and PD2-1 to PD2-2 corresponding to Examples 2-1 to 2-6 and Comparative Examples 2-1 to 2-2 are shown in Table 4.

[0243] Table 3

[0244]

[0245] Table 4

[0246]

[0247] The polishing pads involved in Examples 2-1 to 2-6 showed more excellent comprehensive polishing performance, in which NU was further reduced. Although the NU value of Comparative Example 2-1 was also low, it showed more defects. Comparative Example 2-2 showed poor comprehensive polishing performance. The comprehensive polishing performance of Comparative Example 2-1 and Comparative Example 2-2 is unacceptable in this field.

[0248] It should be noted that, according to the explanation and elaboration of the above description, those skilled in the art to which the present invention belongs may also make changes and modifications to the above embodiments. Therefore, the present invention is not limited to the specific embodiments disclosed and described above, and some equivalent modifications and changes to the present invention should also be within the scope of protection of the claims of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the invention.

Claims

1. A polishing pad, characterized in that: The invention comprises a polishing layer, wherein the polishing layer is a closed-cell elastomer formed by a polyurethane substrate having continuous pore separation, the thermal conductivity of the polishing layer is between 0.04W / (m·K) and 0.075W / (m·K), the ratio of the density SG1 of any point along the diameter direction of the polishing layer to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.096, the surface of the polishing layer is engraved with grooves, the groove shapes include: one or more combinations of concentric circle grooves, radial grooves, arc grooves, XY grid grooves, and dot matrix punching grooves, the difference between the volume V0 of the polishing layer before groove engraving and the volume V after groove engraving and the ratio (V0-V) / V0 of the volume V0 of the polishing layer before groove engraving are between 0.02 and 0.

19.

2. The polishing pad according to claim 1, characterized in that The thermal conductivity of the polishing layer is between 0.048 W / (m·K) and 0.065 W / (m·K).

3. The polishing pad according to claim 1, characterized in that The density of the polishing layer is between 0.4 g / cm 3 ~0.73g / cm 3 Preferably, the density of the polishing layer is between 0.4 g / cm 3 ~0.65g / cm 3 between.

4. The polishing pad according to claim 1, characterized in that The tensile strength of the polishing layer is between 2MPa and 18MPa. Preferably, the tensile strength of the polishing layer is between 7MPa and 14.5MPa.

5. The polishing pad according to claim 1, characterized in that The ratio of the density SG1 of any point of the polishing layer along the diameter direction to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.

075.

6. The polishing pad according to claim 1, characterized in that The difference between the volume V0 of the polishing layer before grooving and the volume V after grooving and the ratio (V0-V) / V0 of the volume V0 of the polishing layer before grooving are between 0.02 and 0.

145.

7. The polishing pad according to claim 1, characterized in that The polyurethane substrate is obtained by reacting a multifunctional isocyanate, a polyol and a curing agent; The multifunctional isocyanate comprises one or more combinations of 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 2,2'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 4,4'-diphenylmethane diisocyanate, 1,5-naphthalene diisocyanate, p-phenylene diisocyanate, m-phenylene diisocyanate, p-xylylene diisocyanate, m-xylylene diisocyanate, ethylene diisocyanate, 2,2,4-trimethylhexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, 1,4-cyclohexane diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, isophorone diisocyanate, and norbornane diisocyanate; The polyol comprises one or more combinations of polytetramethylene ether glycol, polyethylene glycol, polypropylene glycol, ethylene glycol, butanediol, diethylene glycol, neopentyl glycol, 2-methyl-1,3-propanediol, hexanediol, 3-methyl-1,5-pentanediol, 1,4-cyclohexanedimethanol, homopolymers and / or copolymers of ethylene oxide and propylene oxide.

8. The polishing pad according to any one of claims 1 or 7, characterized in that The multifunctional isocyanate comprises one or more combinations of toluene diisocyanate, diphenylmethane diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate; the polyol comprises one or more combinations of polytetramethylene ether glycol, diethylene glycol, butanediol, homopolymers and / or copolymers of ethylene oxide and propylene oxide.

9. The polishing pad according to claim 1, characterized in that A buffer layer is included, wherein the thermal conductivity of the buffer layer is between 0.06 W / (m·K) and 0.09 W / (m·K).

10. The polishing pad according to any one of claims 1 or 9, characterized in that: The ratio of the thermal conductivity of the polishing layer to that of the buffer layer is between 0.5 and 1.

2.

11. A polishing pad, characterized in that: The polishing pad comprises a polishing layer, a buffer layer, an adhesive layer and a back adhesive layer, and the thermal conductivity of the polishing pad is between 0.04 W / (m·K) and 0.09 W / (m·K).

12. The polishing pad according to claim 11, characterized in that The polishing layer is a closed-cell elastomer formed by a polyurethane substrate with continuous pore separation, the thermal conductivity of the polishing layer is between 0.04W / (m·K) and 0.075W / (m·K), the ratio of the density SG1 of any point along the diameter direction of the polishing layer to the minimum density SG0 of the polishing layer along the diameter direction is between 1.002 and 1.096, the surface of the polishing layer is engraved with grooves, and the groove shapes include: one or more combinations of concentric grooves, radial grooves, arc grooves, XY grid grooves, and dot matrix punching grooves, and the difference between the volume V0 of the polishing layer before grooving and the volume V after grooving and the ratio (V0-V) / V0 of the volume V0 of the polishing layer before grooving are between 0.02 and 0.

19.

13. A method for manufacturing a semiconductor device, characterized in that: The method comprises the step of grinding the surface of a semiconductor device wafer using a polishing pad, wherein the polishing pad is the polishing pad according to any one of claims 1 to 10.

14. A method for manufacturing a semiconductor device, characterized in that: The method comprises the step of grinding the surface of a semiconductor device wafer using a polishing pad, wherein the polishing pad is the polishing pad according to any one of claims 11 to 12.

Citation Information

Patent Citations

  • Polishing pad and manufacturing method of semiconductor device

    CN114227530A

  • Polishing pad with window and method of manufacturing same

    CN114670118A

  • Heat dissipation polishing pad and preparation method thereof

    CN116160355A

  • Polishing pads produced by an additive manufacturing process

    US20160107287A1

Cited By

  • Non-woven fabric polishing pad with density gradient in inner ring and outer ring as well as preparation method and application of non-woven fabric polishing pad

    CN121624992A

  • A nonwoven polishing pad having a density gradient in the inner and outer rings, and a method of making and use thereof

    CN121624992B